Palivizumab prophylaxis against respiratory syncytial virus infection in patients younger than 2 years of age with congenital heart disease - Mohammed, Mohammed Hassan A. (Ann Saudi Med, 2021)
BACKGROUND: Respiratory syncytial virus (RSV) is a viral pathogen that causes annual epidemics of lower respiratory tract infection with substantial morbidity and mortality in young children, especially those with congenital heart disease (CHD). Palivizumab is the only immunoprophylaxis therapy approved for RSV infection in infants with hemodynamically significant acyanotic or cyanotic CHD. OBJECTIVE: Identify the compliance rate with vaccination and study the effect of RSV vaccination on hospital admissions. DESIGN: Retrospective descriptive study. SETTING: Cardiac center. PATIENTS AND METHODS: Patient data was obtained from outpatient clinic records, inpatient records, and a surgical database for the period from October 2010 to March 2016. Infants with hemodynamically significant CHD, cyanotic CHD and moderate-to-severe pulmonary hypertension were included in the study. Palivizumab 15/mg/kg was given monthly starting from October, the usual beginning of the epidemic season, with five doses in the first season and six doses in the remaining season scheduled for administration. Patients were interviewed at every clinic visit for any side effects during the previous month, occurrence of any RSV infection and any hospital admission. Selection criteria included RSV vaccination and absence of RSV disease. Patients were excluded if they had RSV infection or a repaired cardiac lesion. MAIN OUTCOME MEASURES: Compliance rate, hospital admission frequency and period of stay. SAMPLE SIZE: 530 during six seasons of RSV epidemics. RESULTS: Fourteen patients (2.6%) developed RSV infection and 13 (2.5%) required hospital admission, but only one patient (0.1%) needed intensive care admission. There were no deaths related to RSV infection; however 11 patients died due to causes unrelated to RSV infection. The average compliance rate was 97%. CONCLUSION: Palivizumab was well tolerated and effective in the prophylaxis of severe RSV infection in children with CHD. As in other studies of palivizumab prophylaxis, we observed a reduction in hospital admissions. LIMITATIONS: Retrospective design. CONFLICT OF INTEREST: None.